Novel dominant and recessive variants in human ROBO1 cause distinct neurodevelopmental defects through different mechanisms. Issue 16 (26th March 2022) - Huang, Yan; Ma, Mengqi; Mao, Xiao; Pehlivan, Davut; Kanca, Oguz; Un-Candan, Feride; Shu, Li; Akay, Gulsen; Mitani, Tadahiro; Lu, Shenzhao; Candan, Sukru; Wang, Hua; et al.
Abstract: The Roundabout (Robo) receptors, located on growth cones of neurons, induce axon repulsion in response to the extracellular ligand Slit. The Robo family of proteins controls midline crossing of commissural neurons during development in flies. Mono- and bi-allelic variants in human ROBO1 (HGNC: 10249) have been associated with incomplete penetrance and variable expressivity for a breath of phenotypes, including neurodevelopmental defects such as strabismus, pituitary defects, intellectual impairment, as well as defects in heart and kidney. Here, we report two novel ROBO1 variants associated with very distinct phenotypes. A homozygous missense p.S1522L variant in three affected siblings with nystagmus; and a monoallelic de novo p.D422G variant in a proband who presented with early-onset epileptic encephalopathy. We modeled these variants in Drosophila and first generated a null allele by inserting a CRIMIC T2A-GAL4 in an intron. Flies that lack robo1 exhibit reduced viability but have very severe midline crossing defects in the central nervous system. The fly wild-type cDNA driven by T2A-Gal4 partially rescues both defects. Overexpression of the human reference ROBO1 with T2A-GAL4 is toxic and reduces viability, whereas the recessive p.S1522L variant is less toxic, suggesting that it is a partial loss-of-function allele. In contrast, the dominant variant in fly robo1 ( p.D413G ) affects protein localization, impairs axonal guidance activity and induces mild phototransduction defects, suggesting that it is a neomorphic allele. In summary, our studies expand the phenotypic spectrum associated with ROBO1 variant alleles.